Integration of Aqidah Akhlak Learning: Efforts to Improve the Quality of Islamic Education - Imam Syafi'i; Kartika Nur Umami; Yahya Aziz; Muhammad Anas Ma'arif (AL-ISHLAH: Jurnal Pendidikan, 2022)
Aqidah akhlak is not only a subject to memorize the theory of the material, but also it emphasizes reflecting the religious values in daily life. Hopefully, this subject can increase the character building of the students. This article aims to describe the planning and implementation of Aqidah Akhlak learning as an improvement in the institution's quality. This research is a type of qualitative research using a case study approach. The data in this study were collected using three methods, namely: observation, interviews, documentation, and triangulation. Data analysis techniques include data reduction, data presentation, and verification. The findings of this study represent an effort made by the management of educational institutions to improve the quality of Islamic education by planning the integration of learning Aqidah Akhlak, which is carried out by integrating handbooks, learning materials, and learning support. In the process of integrating Aqidah learning which is carried out while at school, students use the Arabic language of instruction, as well as handbooks used in education, and learning in dormitories uses the yellow book as a support for learning at school.